VOLUNTEERED GEOGRAPHIC INFORMATION (VGI) APPLICATION FOR MONITORING LAND USE VIOLATION CASE STUDY: CIGANJUR FLOOD - Bayu Purwanto; Anang Wahyu Sejati (Jurnal Riset Informatika, 2021)
Land in DKI Jakarta has problems in land use. Many land-use does not comply with planning. Illegal buildings are often found in areas designated for green open space and river boundaries. Land use monitoring requires the role of information technology. This research uses an open-source-based application to develop easier and cheaper. The application consists of a smartphone-based application for the process of reporting land-use violations with the concept of Volunteered Geographic Information (VGI). The application can directly analyze verified data with spatial planning. The analysis uses overlay analysis to see the location and extent of violations in land use. The results of the analysis can be used as a basis for local governments to impose punishment on illegal buildings and to plan for future cities.